ASSESS MINERS' COORDINATION ABILITIES, KEEP BODY BALANCE, AND VESTIBULAR SENSOR SYSTEM - Jumanov O. S. (Proximus Journal Publishing, 2024)
Is this article highlighter data from an experiment conducted to develop the coordination skills of miners. In the work process studied the number of mistakes made by miners and given to correct exercises. As a result, the number of errors has decreased significantly, and this has a positive effect on the work of miners. Indicators were R<0.05 validity>
Keywords: Coordination movements; body balance; vestibular analyzer